2016
DOI: 10.1155/2016/9174891
|View full text |Cite
|
Sign up to set email alerts
|

Microbial-Physical Synthesis of Fe and Fe3O4 Magnetic Nanoparticles Using Aspergillus niger YESM1 and Supercritical Condition of Ethanol

Abstract: Magnetic Fe and Fe3O4 (magnetite) nanoparticles are successfully synthesized using Aspergillus niger YESM 1 and supercritical condition of liquids. Aspergillus niger is used for decomposition of FeSO4 and FeCl3 to FeS and Fe2O3, respectively. The produced particles are exposed to supercritical condition of ethanol for 1 hour at 300°C and pressure of 850 psi. The phase structure and the morphology measurements yield pure iron and major Fe3O4 spherical nanoparticles with average size of 18 and 50 nm, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…The magnetization curves for APH-MNPs and APC-MNPs composites ( Figure 8 ) also indicate the superparamagnetic behavior. In addition, from the analysis, we observed an increased value for M s and decreased values for M r and H c as compared to other MNPs that were capped by different biocomponents [ 44 , 45 ]. The increase in the M s value of APC-MNPs reflected the lower amount of capping agent as compared with APH-MNPs, which was confirmed by the TGA analysis ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 68%
“…The magnetization curves for APH-MNPs and APC-MNPs composites ( Figure 8 ) also indicate the superparamagnetic behavior. In addition, from the analysis, we observed an increased value for M s and decreased values for M r and H c as compared to other MNPs that were capped by different biocomponents [ 44 , 45 ]. The increase in the M s value of APC-MNPs reflected the lower amount of capping agent as compared with APH-MNPs, which was confirmed by the TGA analysis ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 68%
“…Ferrous sulphate solution was then mixed with 1 g of washed mycelia and shaken for 72 h. Nanoparticles formed were characterized using Transmission electron microscopy (TEM), Scanning electron microscopy (SEM), and Fourier-transform infrared spectroscopy (FTIR). Abdeen et al (2016) have reported the fungi-based intracellular synthesis of magnetic iron and magnetite nanoparticles using Asperigillus niger isolated and cultured over 7 days. According to literature, about 250 mg/mL homogenized mycelia was mixed with precursor salts (FeSO 4 and FeCl 3 ), incubated for 6 days, centrifuged and dried to obtain FeS and Fe 2 O 3 pellets.…”
Section: Microorganism-based Synthesis Of Iron Nanoparticlesmentioning
confidence: 99%
“…Schematic diagram of the biological-physical method for synthesis of magnetic nanoparticles(Abdeen et al, 2016).…”
mentioning
confidence: 99%
“…Apart from plants, actinomycetes, fungi, and algae too facilitate the formulation of nanoparticles under optimum conditions of ambient temperature and pH [45]. Nanoparticles have been synthesized using bacteria and yeast extracts [46][47][48]. Nanoparticles synthesized using plants having traditional medicinal importance have been shown to possess potent biomedical and therapeutic activities both in vivo and in vitro.…”
Section: Sustainability With Green Nanotechnologymentioning
confidence: 99%